"Índices agronómicos y composición química de híbridos de maíz (Zea mays L.) forrajero en dos edades de cosecha - Gamarra Gamarra, Jennifer Jomahira (2015)
The research was conducted at the Experimental Farm "La Maria" at the Faculty of Animal Science (FCP) of the State Technical University of Quevedo (UTEQ). Agronomic indices and chemical composition of forage maize hybrids were evaluated PIONEER 30K73; PIONEER-3041; INDIA INDIA S-810 and S-505 harvest ages V8and R2. Design divided into plots randomized block factorial arrangement of 4 x 2 with four forage maize hybrids (PIONEER 30K73; PIONEER-3041; INDIA S-810 and INDIA S-505) was used and two ages of harvest (V8 and R2) with four replications. Agronomic variables were germination; plant height (ALT); stem diameter (DIAM); number of sheets (NHOJAS); leaf area index (IAF); forage production (PVF) and dry matter production (PMS). The chemical composition was determined in dry matter (DM); crude protein (CP) and inorganic matter (MI). Germination all hybrids had a higher percentage to 98%, PIONEER-3041 showed the highest (p <0.05) and ALT NHOJAS. No difference (p> 0.05) was found in stem diameter. INDIA S-505 had the highest (p <0.05) IAF. The growth stage R2 showed the highest mean ALT, DIAM, NHOJAS and IAF. PIONEER-3041 showed the highest (p <0.05) production of green fodder (kg ha-1). Among hybrids no difference (p> 0.05) in the dry matter production (kg ha-1). In the state of R2 higher (p <0.05) yields of green forage and dry matter were. Hybrid 30K73 and INDIA PIONEER S-505 showed the highest (p <0.05) DM content. The higher (p <0.05) percentage of PB was presented on PIONEER 30K73. The growth stage R2 increased (p <0.05) DM content but decreased (p <0.05) the percentage of PB. No differences in the content of MI among hybrids and phenological stages was found. Keywords: Fodder corn, agronomic rates, growth stages, chemical composition